Ovarian Development by Visual and Histological Investigation of Arius subrostratus (Shovelnose Sea Catfish) from Cochin Estuary, India: Ovarian Development in Aris subrostratus - V., Ambily; Nandan S., Bijoy Nandan (Fishery Technology, 2024)
In this evaluation, both macroscopic and histological level examination of the ovary of Shovelnose Sea catfish Arius subrostratus were carried out to find out its exact maturity stages. During this study, complicated cellular level changes could be observed throughout the entire maturation process of the ovary. The external appearance of ovary was estimated from the fresh fish specimens collected from different parts of Cochin estuary, Kerala, India. Ovary of A. subrostratus were classified into five stages based on morphological examination. Subsequently, oogenesis was explained with the aid of many intricate phases like pre vitellogenic phase, vitellogenic phase and the atretic phase which were further subdivided into the chromatin nucleolar phase, the cortical alveolar phase and the yolk and mature phase and finally the spent phase which contained two types of regenerating oocytes called as post ovulatory follicle and atretic oocyte. Besides, three layers of ovarian walls such as the peritoneum, tunica albuginea and germinal epithelium were noticeable in the context of oogenesis.